Complex pattern of immune evasion in MSI colorectal cancer - Özcan-Wahlbrink, Mine; Janikovits, Jonas; Knebel Doeberitz, Magnus von; Kloor, Matthias (OncoImmunology, 2018)
Mismatch repair (MMR)-deficient cancers accumulate multiple insertion/deletion mutations at coding microsatellites (cMS), which give rise to frameshift peptide neoantigens. The high mutational neoantigen load of MMR-deficient cancers is reflected by pronounced anti-tumoral immune responses of the host and high responsiveness towards immune checkpoint blockade. However, immune evasion mechanisms can interfere with the immune response against MMR-deficient tumors. We here performed a comprehensive analysis of immune evasion in MMR-deficient colorectal cancers, focusing on HLA class I-mediated antigen presentation. 72% of MMR-deficient colorectal cancers of the DFCI database harbored alterations affecting genes involved in HLA class I-mediated antigen presentation, and 54% of these mutations were predicted to abrogate function. Mutations affecting the HLA class I transactivator NLRC5 were observed as a potential new immune evasion mechanism in 26% (6% abrogating) of the analyzed tumors. NLRC5 mutations in MMR-deficient cancers were associated with decreased levels of HLA class I antigen expression. In summary, the majority of MMR-deficient cancers display mutations interfering with HLA class I antigen presentation that reflect active immune surveillance and immunoselection during tumor development. Clinical studies focusing on immune checkpoint blockade in MSI cancer should account for the broad variety of immune evasion mechanisms as potential biomarkers of therapy success.
Gesehen am 10.03.2020